Hasan Hanafi And The Idea Of Deconstruction Of ScienceUshul Fiqh Towards The Reactualization Of Islamic Law - Badruzaman; Hakiki, Kiki Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research examines Hasan Hanafi's thoughts on the deconstruction of ushul fiqh science as an effort to reactualize Islamic law. The results showed four main findings. First, Hasan Hanafi pays great attention to the revitalization of ushul fiqh through a historical approach, by emphasizing the importance of the historical and human dimensions in understanding the concept and methodology. This dimension is actually inherent in the classical methodology of ushul fiqh, but has been obscured as the discipline has developed. For Hanafi, the historical dimension is present in all elements of ushul fiqh, including adillah syar'iyyah, thuruq al-istinbath, and al-ahkam al-syar'iyyah, which are represented through the keywords